Implementasi Pembelajaran Al-Qur’an Hadits dalam Meningkatkan Life Skill Siswa di Madrasah Aliyah Manba’ul Hikam Sidoarjo - Ahmad Zainal Musthofah; Maulana El-Yunusi , Muhammad Yusron (IAI Nasional Laa Roiba Bogor, 2024)
Through the learning skills will be found a form of special skills that suit the students’ talents and interests. Therefore, the special skills were life skills in the sense of special skills which obtained through the learning skills. Thus, the researcher was raised a research title “An implementation of Al-Qur’an Hadith learning in enhancing student life skills at Madrasah Aliyah Manba’ul Hikam Sidoarjo” by means of focusing on lesson planning, learning implementation and learning assessment. Whereas in order to have deep explanation of the students life skills were extracurricular activities, intracurricular and co-curricular activities in the subject of Al-Qur’an Hadith by means of some limitations.Furthermore, the aim of this study was to find out and analyze the implementation of Al-Qur’an Hadith learning in enhancing the life skills of students at Madrasah Aliyah Manba’ul Hikam Sidoarjo. This study is applied by using a qualitative approach, and the data collection is done by interviews, observation and documentation. While, the analysis techniques is used data reduction, data presentation and drawing conclusion.The result of this study can be summarized as follows, life skills of students who are improved at Madrasah Aliyah Manba’ul Hikam Sidoarjo are carried out through two activities, namely extracurricular activities (there are mandatory extracurriculars namely scouting and there are several elective extracurriculars) and also the enhancing skills through Al-Qur’an Hadith learning.Second, the implementation of Al-Qur’an Hadith learning in enhancing the life skills of students at Madrasah Aliyah Manba’ul Hikam Sidoarjo with three stages of lesson planning, learning implementation and learning assessment.Later, that future researchers will conduct more in – depth research on the implementation of Al- Qur’an Hadith learning in enhancing students’ life skills.